Checklist of digenean parasites of birds from Argentina - Lunaschi, Lía I.; Cremonte, Florencia; Drago, Fabiana B. (Zootaxa, 2007)
Helminth parasites of birds have been studied in Argentina for almost one century. Survey work on this group of parasites is far from complete. Here we present a checklist that summarizes the diversity of digeneans of birds from Argentina, each account is based on a literature search and gives, for each digenean species, their hosts, site of infection, localities, life cycle if known, and collection number of types where they are housed. Moreover, it presents a list of bird hosts with their digenean parasites and a list of intermediate hosts. To date, 95 digenean species have been reported; of which 27 species (29%) were new to science. These reports include 2 species of Brachylaimoidea, 2 Clinostomoidea, 5 Cyclocoeloidea, 3 Dicrocoelioidea, 21 Diplostomoidea, 26 Echinostomatoidea, 1 Gymnophalloidea, 10 Microphalloidea, 12 Opisthorchioidea, 1 Paramphistomoidea, 8 Pronocephaloidea, 2 Schistosomatoidea and 1 Troglotrematoidea. A total of 60 wild and domestic species of birds have been reported as natural hosts of digeneans in Argentina and 5 species as experimental hosts.